Women's regional rights : the League of Arab States / P.A. van Laar & W.J.F.M. van der Wolf (eds). - Laar, P. A. van.; Wolf, Willem-Jan van der. (Wolf Legal Publishers, 2009)
Chiefly reports of the UN Committee on the Elimination of Discrimination Against Women (CEDAW).